2017
DOI: 10.1371/journal.pone.0178454
|View full text |Cite
|
Sign up to set email alerts
|

Leptin signals via TGFB1 to promote metastatic potential and stemness in breast cancer

Abstract: Epidemiological studies have shown obesity to be linked with poorer outcomes in breast cancer patients. The molecular mechanisms responsible for the increased risk of invasive/metastatic disease with obesity are complex, but may include elevated levels of adipokines such as leptin. Using physiological levels of leptin found in obesity in a novel chronic in vitro treatment model (≤200 ng/ml for 14 days), we confirmed the occurrence of leptin-mediated changes in growth, apoptosis and metastatic behavior, and gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 65 publications
1
46
1
Order By: Relevance
“…TGFB1 binds the TGFB receptor, leading to the phosphorylation and nuclear translocation of SMAD2 and SMAD3, which mediate proliferation, differentiation, migration and cancer stemness by binding to transcription factors such as SMAD4 . TGFB1 suppresses oncogenesis by regulating proliferation, although it promotes cancer progression by contributing to invasion and metastasis of established tumors . Evidence indicates that TGFB1 mediates tumor progression in concert with FRAS1, because FRAS1 is expressed in cancer tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TGFB1 binds the TGFB receptor, leading to the phosphorylation and nuclear translocation of SMAD2 and SMAD3, which mediate proliferation, differentiation, migration and cancer stemness by binding to transcription factors such as SMAD4 . TGFB1 suppresses oncogenesis by regulating proliferation, although it promotes cancer progression by contributing to invasion and metastasis of established tumors . Evidence indicates that TGFB1 mediates tumor progression in concert with FRAS1, because FRAS1 is expressed in cancer tissues.…”
Section: Discussionmentioning
confidence: 99%
“…35 TGFB1 suppresses oncogenesis by regulating proliferation, although it promotes cancer progression by contributing to invasion and metastasis of established tumors. 36 Evidence indicates that TGFB1 mediates tumor progression in concert with FRAS1, because FRAS1 is expressed in cancer tissues. AHNAK is associated with tumor progression 37 or suppression and increases signaling through the TGFB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…-catenin can be relocated into the nucleus where acts as a transcription factor forming complexes with DNA binding proteins such as TCF/LEF [89,90]. In this study, we observed that β-catenin expression increases in leptin-stimulated cells in addition to a nuclear relocation of β-catenin at 3 h. These findings might be related to the decrease in the expression or changes in the location of proteins at adherent junctions, particularly, Ecadherin and β-catenin plays an important role in the induction of EMT [91].…”
Section: Discussionmentioning
confidence: 99%
“…73 Leptin induces TGFb1 expression, decreases the epithelial marker Ecadherin and increases EMT marker SNAI2 in BC cells. 74 In addition, leptin increases the CD44 1 /CD24 2 stem cell population in BC cells. 75 HER2 and leptin have mutual inductive effects and leptin decreases the sensitivity to anti-HER2 interventions in HER2 1 BC.…”
Section: Determinants Of Bc Risk: Considerations For Bc Prevention Anmentioning
confidence: 97%
“…Interestingly, many breast tumors also express leptin receptors which are positively associated with BC proliferation . Leptin induces TGFβ1 expression, decreases the epithelial marker E‐cadherin and increases EMT marker SNAI2 in BC cells . In addition, leptin increases the CD44 + /CD24 − stem cell population in BC cells .…”
Section: Determinants Of Bc Risk: Considerations For Bc Prevention Anmentioning
confidence: 99%